The Lack of Integration in E-Blud Implementation: A Critical Hot-Fit Framework Approach - Surya, Rio Ageng (Master in Accounting Program, 2024)
This research examines the implementation of the Electronic Public Service Agency Financial Management System (E-BLUD) in health centers (Puskesmas) in Wonogiri Regency. Over the past two years since its implementation, there has been no external evaluation of financial reporting changes. Using the HOT-Fit Framework, this study employs a qualitative approach to understand the impact of the integration between human, organization, and technology on the net benefits derived from the implementation of E-BLUD. The findings reveal that despite the good information quality and fast response from vendor services, the system's quality has not been optimal. Moreover, there are significant challenges in system integration, comprehension of Government Accounting Standards, and the lack of professional accountants in each Puskesmas. While E-BLUD has been developed to enhance financial reporting processes within Puskesmas, the existence of normative user satisfaction and intentions to use, alongside the lack of full organizational support, high dependence on external factors, and the net benefits produced, indicate substantial room for further development.Keywords: E-BLUD, Puskesmas, HOT-Fit Framework, System Integration.